Vegetation water use efficiency constrains the dynamic of net primary productivity in Mu Us Sandy Land - Chen, Yunfei; Liu, Zuyu; Guo, Xinjia; Liu, Kun; Zhang, Leyi; Liu, Jing; Liu, Xiuhua; He, Junqi (Frontiers in Plant Science, 2026)
The Mu Us Sandy Land (MUSL) in Northwest China, once one of the world’s most severely desertification areas, is now a leading example of successful ecological restoration. Undoubtedly, ecological restoration efforts have significantly reversed this region’s desertification and enhanced carbon sequestration. However, uncertainties remain regarding whether ongoing and expanded restoration initiatives can continue to stabilize or further enhance the productivity and carbon sequestration capacity of the region’s ecosystems. Net primary productivity (NPP) as an important indicator for evaluating ecosystem function and sustainability. Analyzing its spatial-temporal evolves differences and driving mechanisms is crucial for formulating effective ecological restoration policies. Given this, this study applied the Breaks for Additive Season and Trend (BFAST) method to diagnose the NPP’s spatiotemporal dynamics and development patterns in the MUSL from 2001 to 2020. The results revealed significant temporal-spatial variations in NPP, identifying eight development patterns (Type1-8). Among these, three increasing trends patterns—Type1, Type3, and Type5—were dominant, driven by rising regional precipitation and temperature, accounting for 82.9% of the total areas. In contrast, in the southern area with more favorable hydrothermal conditions, Type7 (from increase to decrease) was dominated, accounting for 16.4%. NPP in this region initially increased from 52 gC·m-2 to 117 gC·m-2, before declining to 70 gC·m-2, reflecting a notable decline. The structural equation model’s results indicated that although the high synergistic effect between climatic factors and ecological restoration significantly promoted the rapid increase of NPP in most areas of the MUSL, it might not alter the declining NPP in the southern regions (Type7) with more favorable hydrothermal conditions, where vegetation shows low response to precipitation. While further analysis indicated that reaching the threshold of water use efficiency is one of a significant reason for the decline in NPP in the southern region. Overall, these findings and insights not only provide reliable data and guidance for future ecological restoration projects, but also serve as a crucial warning for vegetation management in arid regions.